Dynamic Simulations of Parkinson’s Disease and ALS Propagation in the Brain: A Reaction-Diffusion on Brain Networks Approach - Zaidan Al Arsyad; Faiz Munir; Amanda Allawiyah; Tiara Sania; Irvan Hartawan; Prama Putra (Jambura Journal of Biomathematics (JJBM), 2025)
Neurodegenerative diseases,  such  as  Parkinson’s Disease  (PD)  and  Amyotrophic Lateral  Sclerosis  (ALS), progressively degrade neural systems, leading to considerable cognitive functional disorders. It is consequential to comprehend how these diseases spread within the brain to develop precise diagnoses and interventions. This study uses a reaction-diffusion model on a human brain network model to explore and replicate the actual dynamic progression of PD and ALS. By incorporating diffusion processes with empirical brain network data, we simulated the disease’s progression through various regions. Our results show unique propagation patterns for PD and ALS and the effect of different network models on disease transmission.  The structure of brain neural networks plays a vital function in neurodegeneration and offers insights that lead to early detection and focused treatments. This study presents a potential viewpoint on handling and interfering in neurodegenerative diseases by perceiving their dependency on brain neural connectivity.